Socio-philosophical grounding of the conception of proletarian culture - Kolychev, P.M.; Khakhalova, A.A. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Filosofii͡a, 2018)
The currency of the research consists in the necessity if rethinking of the notion of culture in Russian contemporary thought in order to present more adequately the process of development of culture in a future. The paper aims to elucidate political origins of the movement of Proletarian culture that play the leading role in a creation of a new conception of culture. As a materials were used documents and archives, scientific paper of Russian and foreign researchers. As a maim method was used problematic-analytical reconstruction, explored in the framework of an enactive approach that allows to envelop the subject in its evolvement and to concentrate on concrete practical situations of its realization. Such reconstruction permits to accomplish the original interpretation of the problem. The authors focus in the pre-history of the movement. Analyzing the social-political context of the origin of the movement, the authors come to the conclusion about artificially created necessity of political enlightenment of the society by the revolutionaries. The paper demonstrates how agents of proletarian working circles manipulate by the public opinion of working class. As a result, the paper shows the process of formation the ideology of cultural movement revolutionary period and evaluates significance of ideological function in its realization. The authors produce critical evaluation of the history of the movement in original judgment about political grounding of culture.